Design and optimization of an ultra-sensitive hairpin DNA aptasensor for Salmonella detection. Issue 56 (12th July 2017) - Lee, Jayeon; Jung, Juyeon; Lee, Chang Soo; Ha, Tai Hwan
Abstract : A simple scheme using a hairpin DNA aptasensor was established to detect Salmonella Typhimurium ( S. Typhimurium). Abstract : A simple scheme using a hairpin DNA aptasensor was established to detect Salmonella Typhimurium ( S. Typhimurium). The hairpin DNA aptasensor was a single-stranded oligonucleotide including both a target-binding sequence and a reporting DNAzyme called horseradish peroxidase-mimicking G-quadruplex. Four hairpin DNA aptasensors were investigated to optimize the sequence with two enzymatic substrates for different signaling modes. Covalent conjugation of hemin on an aptasensor strand was preliminarily executed in colorimetric assays and then conducted with p -coumaric acid in chemiluminescence assays, to lower the background signal arisen from free hemin. A limit of detection (LOD) of this detection scheme was 100 CFU mL −1 in colorimetric assays and was even further improved to 2 CFU mL −1 in chemiluminescent assays. The present detection scheme is expected to have application as a simple, rapid method for detection of various types of hazardous targets.